A case of digital hoarding. (8th October 2015) - van Bennekom, Martine J; Blom, Rianne M; Vulink, Nienke; Denys, Damiaan
Abstract : A 47-year-old man presented to our outpatient clinic, preoccupied with hoarding of digital pictures, which severely interfered with his daily functioning. He was formerly diagnosed with autism and hoarding of tactile objects. As of yet, digital hoarding has not been described in the literature. With this case report, we would like to introduce 'digital hoarding' as a new subtype of hoarding disorder. We conclude with differential diagnostic considerations and suggestions for treatment.